IL-10 Counteracts Proinflammatory Mediator Evoked Oxidative Stress in Caco-2 Cells - Eva Latorre; Nyurky Matheus; Elena Layunta; Ana Isabel Alcalde; José Emilio Mesonero (Hindawi Limited, 2014)
Oxidative stress is thought to play a key role in the development of intestinal damage in intestinal inflammatory diseases. Several molecules are involved in the intestinal inflammation, either as pro- or anti-inflammatory factors; however, their effects on intestinal oxidative stress seem to be controversial. This work analyzes the contribution of pro- and anti-inflammatory molecules to the balance of oxidative damage in intestinal epithelial cells, as well as their effects on cellular antioxidant enzyme activity. With this purpose, the lipid and protein oxidation, together with the activity of catalase, superoxide dismutase, and glutathione peroxidase, were determined in the Caco-2 cells treated with serotonin, adenosine, melatonin, and TNFα, as proinflammatory factors, and IL-10, as an anti-inflammatory cytokine. The results have shown that all the proinflammatory factors assayed increased oxidative damage. In addition, these factors also inhibited the activity of antioxidant enzymes in the cells, except melatonin. In contrast, IL-10 did not alter these parameters but was able to reduce the prooxidant effects yielded by serotonin, adenosine, melatonin, or TNFα, in part by restoring the antioxidant enzymes activities. In summary, proinflammatory factors may induce oxidative damage in intestinal epithelial cells, whereas IL-10 seems to be able to restore the altered redox equilibrium in Caco-2 cells.